Early post-stroke cognitive impairment and in-hospital predicting factors among stroke survivors in Ethiopia - Ayehu, Gashaw Walle; Admasu, Fitalew Tadele; Yitbarek, Getachew Yideg; Agegnehu Teshome, Assefa; Amare, Abraham Tsedalu; Atlaw, Daniel; Sharma, Saurab (Frontiers in Neurology, 2023)
Background: In low- and middle-income countries, Post-Stroke Cognitive Impairment (PSCI) is the least investigated stroke complication that clinically is given little attention. Finding patients who are at high risk for continuing cognitive problems after a stroke could allow for targeted follow-up and help with prognosis discussions, which would then contribute to improved treatment outcomes. The main aim of this study was to determine the incidence and predictors of PSCI among stroke survivors in Northwest Ethiopia. Methods: The study was a multicenter prospective cohort study. The study participants were 403 stroke survivors who were alive after three months of stroke onset and on follow-up at the neurology department of three hospitals in Northwest Ethiopia. To investigate the link between the outcome and the explanatory variables, analyses of bivariable and logistic multivariable regression were performed. A p-value of 0.05 or less was regarded as statistically significant and data were presented as odds ratios and 95% confidence intervals. Results: The mean age of the participants was 61.3 years (SD=0.7), 56% were females, the mean time from symptom onset to hospital arrival was 46 hours (SD=3.32), and the mean National Institute of Health Stroke Scale (NIHSS) score at admission was 14.79 (SD=0.25). PSCI was observed in 122 (30.3%) after ninety days of stroke onset that is 83 (20.6%) of female and 39 (9.7%) of male stroke survivors. The result of multivariable logistic regression analysis revealed PSCI was independently associated with age (adjusted OR= 1.04, 95% CI=1.061-1.981), Females (AOR=1.390, 95% CI=1.221-2.690), admission modified rankin scale (mRS) (AOR=1.629, 95% CI=1.381-2.037), moderate Glasgow coma scale (GCS) score (AOR=1.149, 95% CI=1.402-3.281), and poor GCS score (AOR=1.632, 95% CI=1.610-4.361) and stage one (AOR=1.428, 95% CI=1.198-2.922) and stage two hypertension (AOR=1.255, 95% CI=1.107-2.609). Conclusion: Nearly one-third of stroke survivors developed PSCI. Moreover, further research is needed with a larger sample size, showing time trend and longer follow-up duration.